Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/0379572116679053
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Outpatient Ready-To-Use Food-Based Protocols in HIV-Infected Senegalese Children and Adolescents Within the MAGGSEN Cohort Study

Abstract: NCT01771562 (Current Controlled Trials).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
10
1
Order By: Relevance
“…The observed level of adherence in this study is higher than the previous study conducted in the study area where 36.3% of the PLWHA were found to be adherent to the FBP program (Kebede and Haidar, 2014). However, the equivalent finding was reported from Senegal where the rate of RUTF consumption compared to the prescribed amount was approximately 50% among the study subjects (Cames et al, 2017). A qualitative study conducted in Kenya also revealed that half of malnourished AIDS adult patients failed to consume the daily prescription of RUTF (Dibari et al, 2011).…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The observed level of adherence in this study is higher than the previous study conducted in the study area where 36.3% of the PLWHA were found to be adherent to the FBP program (Kebede and Haidar, 2014). However, the equivalent finding was reported from Senegal where the rate of RUTF consumption compared to the prescribed amount was approximately 50% among the study subjects (Cames et al, 2017). A qualitative study conducted in Kenya also revealed that half of malnourished AIDS adult patients failed to consume the daily prescription of RUTF (Dibari et al, 2011).…”
Section: Discussioncontrasting
confidence: 82%
“…The study conducted in Addis Ababa City also reported sharing the product with children and with other HIV-infected friends (Kebede and Haidar, 2014). The practice of sharing the RUTF with household members was also reported from similar studies conducted elsewhere (Gerberg and Stansbury, 2010;Dibari et al, 2011;Cames et al, 2017). The scarcity of food at the level of households, poverty, household food insecurity, and cultural issues are among the reasons behind sharing RUTF (Rodas-Moya et al, 2015;Food and Nutrition Technical Assistance, 2009;Kebede and Haidar, 2014).…”
Section: Discussionmentioning
confidence: 74%
“…Qualitative studies conducted in Southern Africa reported poor overall acceptability of RUF [16][17][18], whereas its organoleptic qualities were rated as good in studies from Vietnam [19] and Haiti [20]. Assessment of a pilot nutrition support providing RUF to 43 HIVinfected children and adolescents with acute malnutrition in two HIV clinics in Senegal shown that beneficiaries consumed 50% of their RUF on average and 20% defaulted from the programme [21]. Following this pilot study, the SNACS Study was implemented to assess the acceptability, effectiveness, and feasibility of outpatient RUF-based nutritional therapy among HIV-infected children and adolescents presenting with acute malnutrition across Senegal.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative studies conducted in Southern Africa reported poor overall acceptability of RUF (16)(17)(18), whereas its organoleptic qualities were rated as good in studies from Vietnam (19) and Haiti (20). Assessment of a pilot nutrition support providing RUF to 43 HIV-infected children and adolescents with acute malnutrition in two HIV clinics in Senegal shown that beneficiaries consumed 50% of their RUF on average and 20% defaulted from the programme (21). Following this pilot study, the SNACS Study was implemented to assess the acceptability, effectiveness, and feasibility of outpatient RUF-based nutritional therapy among HIV-infected children and adolescents presenting with acute malnutrition across Senegal.…”
Section: Introductionmentioning
confidence: 99%